STUDENT'S PERCEPTIONS TOWARDS PRONUNCIATION FEEDBACKS IN ENGLISH SPEAKING ACTIVITY THROUGH ELSASPEAK TASK - Sindi Nurhayati Hermina; Setia Muljanto; Pipih Setiaawati; Muhammad Soni; R Muhammad Satria Gyas Mustagis (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
English pronunciation is essential for effective oral communication, yet it remains a persistent challenge for Indonesian junior high school students, particularly in terms of accuracy and speaking confidence. Recent advances in artificial intelligence, especially Computer-Assisted Pronunciation Training (CAPT), have introduced new opportunities for providing immediate and personalized pronunciation feedback. This descriptive qualitative study explored ninth-grade students’ perceptions of pronunciation feedback provided by the ELSA Speak application and examined the reasons underlying these perceptions. The study was conducted at SMPN 6 Garut and involved 34 ninth-grade students selected through purposive sampling. Data were collected through weekly reflective journals, classroom observations during pronunciation practice, and documentation of pronunciation scores generated by the application. The data were analyzed using thematic analysis to identify recurring patterns in students’ experiences. The findings reveal a clear polarization in students’ perceptions. Some students benefited from ELSA Speak due to its safe practice environment, visual feedback, and support for autonomous learning, while others experienced technical frustration, limited articulatory explanations, and digital fatigue caused by repetitive practice and reduced human interaction. The study concludes that ELSA Speak is not a one-size-fits-all solution and is most effective when used as a supplementary tool supported by teacher guidance. Further research is recommended to examine the role of teacher mediation and long-term use of AI-based pronunciation tools in diverse learning contexts. ABSTRAK Pelafalan bahasa Inggris merupakan aspek penting dalam komunikasi lisan, namun masih menjadi tantangan bagi siswa sekolah menengah pertama di Indonesia, terutama terkait ketepatan fonologis dan kepercayaan diri berbicara. Perkembangan teknologi kecerdasan buatan, khususnya Computer-Assisted Pronunciation Training (CAPT), menawarkan peluang baru melalui penyediaan umpan balik pelafalan yang bersifat langsung dan personal. Penelitian kualitatif deskriptif ini bertujuan untuk mengeksplorasi persepsi siswa kelas IX terhadap umpan balik pelafalan yang diberikan oleh aplikasi ELSA Speak serta mengidentifikasi alasan di balik persepsi tersebut. Penelitian ini dilaksanakan di SMPN 6 Garut dengan melibatkan 34 siswa kelas IX yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui jurnal reflektif mingguan, observasi kelas selama latihan pelafalan, serta dokumentasi skor pelafalan dari aplikasi. Data dianalisis menggunakan teknik analisis tematik untuk mengidentifikasi pola pengalaman siswa. Hasil penelitian menunjukkan adanya polarisasi persepsi siswa. Sebagian siswa merasakan manfaat dari ELSA Speak karena lingkungan latihan yang aman, umpan balik visual yang jelas, dan dukungan terhadap pembelajaran mandiri. Sebaliknya, siswa lain mengalami frustrasi teknis, keterbatasan penjelasan artikulatoris, serta kelelahan digital akibat latihan yang repetitif dan minim interaksi manusia. Penelitian ini menyimpulkan bahwa ELSA Speak bukan solusi tunggal pembelajaran pelafalan dan lebih efektif digunakan sebagai alat pendukung dengan bimbingan guru. Penelitian selanjutnya disarankan untuk mengkaji peran mediasi guru dan penggunaan jangka panjang teknologi CAPT dalam konteks pembelajaran yang beragam.